2018
DOI: 10.3390/w10030305
|View full text |Cite
|
Sign up to set email alerts
|

Energetic, Exergetic, and Economic Analysis of MED-TVC Water Desalination Plant with and without Preheating

Abstract: Desalination is the sole proven technique that can provide the necessary fresh water in arid and semi-arid countries in sufficient quantities and meet the modern needs of a growing world population. Multi effect desalination with thermal vapour compression (MED-TVC) is one of most common applications of thermal desalination technologies. The present paper presents a comprehensive thermodynamic model of a 24 million litres per day thermal desalination plant, using specialised software packages. The proposed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The preheating of feed to a higher temperature yields more freshwater. 51 Similarly, from Figure 5d, it can be inferred that a higher motive steam pressure favors a higher PR, which is consistent with the study reported by ref 52. The last effect of brine temperature (T B,N ) determines the temperature driving force of the process.…”
Section: Moo Of Med-tvc 721 Sensitivity Analysissupporting
confidence: 91%
“…The preheating of feed to a higher temperature yields more freshwater. 51 Similarly, from Figure 5d, it can be inferred that a higher motive steam pressure favors a higher PR, which is consistent with the study reported by ref 52. The last effect of brine temperature (T B,N ) determines the temperature driving force of the process.…”
Section: Moo Of Med-tvc 721 Sensitivity Analysissupporting
confidence: 91%
“…The theoretical lowest separation energy of seawater of concentration 35000 mg/L and temperature of 28°C is around 0.78 kWh/m 3 [17,18]. Unfortunately, all practical desalination technologies, such as multi effect desalination (MED) [19][20][21][22][23][24][25][26], multi stage flash (MSF) [27][28][29] and Seawater reverse osmosis (SWRO) [30,31] are operating at 8-10 times higher than theoretical minimum energy requirement or thermodynamic limit (TL). Almost 95% online desalination capacity is based on these three major but practical processes.…”
Section: Separation Processesmentioning
confidence: 99%
“…With more technological advancement such as coupling with thermo vapor compression (TVC) for lower temperature operation has promoted the economic feasibility hence the sharp increase in MED application in desalination market. [ 18 ] In VC, the vapor is compressed to generate heat for evaporating the seawater. Two methods are used, i.e., mechanical vapor compression (MVC) and TVC in which the vapor generated in the evaporator is compressed mechanically and thermally, respectively.…”
Section: Performance and Energy Consumption Of Desalination Processesmentioning
confidence: 99%